Down syndrome and postoperative hemodynamics in patients undergoing surgery for congenital cardiac communications - Eloisa Sassá Carvalho; Juliano Gomes Penha; Nair Yukie Maeda; Kelly Cristina O. Abud; Maria Francilene S. Souza; Claudia R. P. Castro; Johnny X. dos Santos; Juliana Pereira; Antonio Augusto Lopes (Scientific Reports)
Abstract Although Down syndrome (DS) is considered a risk factor for hemodynamic instabilities (mainly pulmonary hypertension–PH) following surgery for congenital cardiac communications, many DS patients do surprising well postoperatively. We prospectively analyzed perioperative factors for a possible correlation with post-cardiopulmonary bypass (CPB) inflammatory reaction and postoperative PH in pediatric subjects. Sixty patients were enrolled (age 3 to 35 months), 39 of them with DS. Clinical and echocardiographic parameters (anatomical and hemodynamic) were computed preoperatively. Pulmonary and systemic mean arterial pressures (PAP and SAP) were assessed invasively intra and postoperatively. Immediate postoperative PAP/SAP ratio (PAP/SAPIPO) and the behavior of pressure curves were selected as primary outcome. Serum levels of 36 inflammatory proteins were measured by chemiluminescence preoperatively and 4 h post CPB. Of all factors analyzed, peripheral oxygen saturation (O2Sat, bedside assessment) was the only preoperative predictor of PAP/SAPIPO at multivariate analysis (p = 0.007). Respective values in non-DS, DS/O2Sat ≥ 95% and DS/O2Sat < 95% subgroups were 0.34 (0.017), 0.40 (0.027) and 0.45 (0.026), mean (SE), p = 0.004. The difference between non-DS and DS groups regarding postoperative PAP curves (upward shift in DS patients, p = 0.015) became nonsignificant (p = 0.114) after adjustment for preoperative O2Sat. Post-CPB levels of at least 5 cytokines were higher in patients with O2Sat < 95% versus those at or above this level, even within the DS group (p < 0.05). Thus, a baseline O2Sat < 95% representing pathophysiological phenomena in the airways and the distal lung, rather than DS in a broad sense, seems to be associated with post-CPB inflammation and postoperative PH in these patients.